1993
DOI: 10.1093/glycob/3.6.567
|View full text |Cite
|
Sign up to set email alerts
|

Low-sulphated oligosaccharides derived from heparan sulphate inhibit normal angiogenesis

Abstract: Heparin, with or without the addition of an adrenocorticosteroid, can inhibit normal angiogenesis in the chick embryo chorioallantoic membrane. Low- or non-sulphated heparin fragments also have anti-angiogenic effect. Attempts to define a saccharide structure responsible for the anti-angiogenic effect implicated a -[GlcA beta 1,4-GlcNAc alpha 1,4]n-sequence. This structure represents the product of the initial polymerization reaction in heparin/heparan sulphate biosynthesis. It persists in the non-sulphated re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 0 publications
2
18
0
Order By: Relevance
“…Functionally, this might indicate that vascular basement membranes are capable of binding leukocytes, which constitutively express L-selectin on their cell surface. Other potential important biological activities of vascular HS, to be considered in this context, include anti-proliferative effect on arterial smooth muscle cells (16), inhibition of mesangial cell growth (55), and inhibition of angiogenesis (56).…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, this might indicate that vascular basement membranes are capable of binding leukocytes, which constitutively express L-selectin on their cell surface. Other potential important biological activities of vascular HS, to be considered in this context, include anti-proliferative effect on arterial smooth muscle cells (16), inhibition of mesangial cell growth (55), and inhibition of angiogenesis (56).…”
Section: Discussionmentioning
confidence: 99%
“…Heparin binds to different cell types and to various plasma proteins, thereby modulating their activity [1][2][3][4]. One could therefore argue that the inhibitory effects of LMWH described above might be attributed to its binding to these cytokines.…”
Section: Lmwh Inhibits Production But Does Not Bind Tnf-amentioning
confidence: 99%
“…Beyond its well understood anticoagulant activity, heparin is known to bind and modulate the activity of various proteins, including cell growth and angiogenic factors [1,2], complement components [3] and adhesion molecules [4]. Heparin also exerts anti-inflammatory activities through interacting with different cell types and modulating their proinflammatory activities by interfering with various processes such as migration and cytokine production [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Analogous results were obtained on low-sulphated heparan sulphate derivatives by another research group, Hahnenberger R et Al. 1993 [5]. Interestingly this research group found an higher activity in oligosaccharide containing iduronic acid residues ; this exuronic acid is tipically present in heparin more then in heparan sulfate.…”
Section: Discussionmentioning
confidence: 92%